Labor‐saving technologies in Manantali, Mali. Issue 2 (23rd April 2021) - Koenig, Dolores
Abstract : Facing enduring labor shortages, West Africans have long adopted labor‐saving technologies. Using data from a study of 108 households in 2016–18 in Manantali, Mali, this article looks at the availability, adoption, uses, and outcomes of common labor‐saving technologies in agriculture, domestic provision, transport, and telecommunications. People were attracted by technologies that they deemed useful. Locally available and relatively inexpensive technologies were more readily adopted than more expensive devices that required sophisticated management. The adoption of labor‐saving devices in one sphere of activity often had spillover effects into others. For example, the use of labor‐saving devices in food preparation allowed women to spend more time in agriculture. In turn, greater production gave women more produce to sell and more income to address personal and collective needs. The adoption of labor‐saving devices led to only incremental changes in global and local hierarchies, in part because people adopted many technologies so that they could maintain aspects of their life in changing circumstances. Although industrially produced goods mostly came from outside Mali, many locals learned to repair imported technologies, and some spare parts were locally made. As women demonstrated their ability to use greater resources to make village‐wide contributions, local hierarchies of gender have been attenuated.